Sublethal and lethal exposure to broflanilide disrupt sex pheromone biosynthesis signaling and reproductive success in the Spodoptera frugiperda - Zelong She; Ruolan He; Xianxue Song; Qisheng Song; Jizhen Wei; Mengfang Du; Xinming Yin; Shuangyan Yao; Shiheng An (Pesticide Biochemistry and Physiology, 2026)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

MicroRNA-592 suppresses breast cancer progression by targeting CYP20A1 to modulate the CHOP pathway - Ruolan Pan; Shangquan Jiang; Jinxing Su; Caiyun Zhang; Xiaoxing Li; Kan He (Journal of Physiology and Biochemistry, 2025)

Therapeutic potential of Angelica sinensis derivatized carbon dots in ameliorating chemotherapy-induced anemia - Ruolan Kong; Yujiao Yuan; Jiaxing Liu; Kai Cheng; Yifan Zhang; Xiwen Zhang; Peng Zou; Yan Huang; Jinyu Ma; Chenxin He; Hui Kong; Yan Zhao; et al. (Journal of Molecular Histology, 2025)

Gender differences in commuting travel mode choices among young adults: A spatial heterogeneity perspective - Yang Liu; Ruolan Shen; Mingwei He; Xuefeng Li; Zhuangbin Shi (Journal of Transport Geography, 2025)

PKC phospho-activated PFK1 is required for PBAN regulated sex pheromone biosynthesis in Helicoverpa armigera - Ruolan He; Zelong She; Yao Zhang; Shuangyan Yao; Jizhen Wei; Mengfang Du; Shiheng An (Journal of Insect Physiology, 2025)

Correlation analysis and modeling application from objective indicators to subjective evaluation of scented tea: A case study of rose tea - Ruolan Song; Meng Shen; Yanran Wang; Youyi Sun; Jiamu Ma; Qingyue Deng; Xueyang Ren; Xianxian Li; Yuan Zheng; Yingyu He; Feng Zhang; Mingxia Li; et al. (Food Chemistry, 2025)

Rapid Joule heating-induced welding of silicon and graphene for enhanced lithium-ion battery anodes - Fan Yang; Pengcheng Deng; Hang He; Ruolan Hong; Kun Xiang; Yuan Cao; Beibei Yu; Zeman Xie; Jiming Lu; Zikang Liu; Danish Khan; David Harbottle; et al. (Chemical Engineering Journal, 2024)

Rapid and highly sensitive colorimetric LAMP assay and integrated device for visual detection of monkeypox virus - Yadan Peng; Ruolan Hu; Shuang Xue; Yugan He; Lili Tian; Zehan Pang; Yile He; Yuqi Dong; Yinghan Shi; Shuqi Wang; Bixia Hong; Ke Liu; et al. (Analytica Chimica Acta, 2024)

Acceleration of the charge transfer rate for efficient photocatalytic hydrogen production via adjusting modulator and introducing electronic bridge dual strategies - Xingyan Liu; Haibo Zhou; Ruolan Li; Maosen Xu; Chenghua Zhang; Zhengsijia Wu; Youzhou He; Xu Zou; Min Fu; Siping Wei (Fuel, 2024)

Plasma-Free Blood as a Potential Alternative to Whole Blood for Transcriptomic Analysis - Qingwang Chen; Xiaorou Guo; Haiyan Wang; Shanyue Sun; He Jiang; Peipei Zhang; Erfei Shang; Ruolan Zhang; Zehui Cao; Quanne Niu; Chao Zhang; Yaqing Liu; et al. (Phenomics, 2024)
RNA sequencing (RNAseq) technology has become increasingly important in precision medicine and clinical diagnostics, and emerged as a powerful tool for identifying protein-coding genes, performing differential gene analysis, and inferring immune cell composition. Human peripheral blood samples are widely used for RNAseq, providing valuable insights into individual biomolecular information. Blood samples can be classified as whole blood (WB), plasma, serum, and remaining sediment samples, including plasma-free blood (PFB) and serum-free blood (SFB) samples that are generally considered less useful byproducts during the processes of plasma and serum separation, respectively. However, the feasibility of using PFB and SFB samples for transcriptome analysis remains unclear. In this study, we aimed to assess the suitability of employing PFB or SFB samples as an alternative RNA source in transcriptomic analysis. We performed a comparative analysis of WB, PFB, and SFB samples for different applications. Our results revealed that PFB samples exhibit greater similarity to WB samples than SFB samples in terms of protein-coding gene expression patterns, detection of differentially expressed genes, and immunological characterizations, suggesting that PFB can serve as a viable alternative to WB for transcriptomic analysis. Our study contributes to the optimization of blood sample utilization and the advancement of precision medicine research.

Combined exposure of beta-cypermethrin and emamectin benzoate interferes with the HPO axis through oxidative stress, causing an imbalance of hormone homeostasis in female rats - Yuxin Li; Xianzhi He; Bin Sun; Nannan Hu; Jiamin Li; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Reproductive Toxicology, 2024)

Enhanced dandelion phytoremediation of Cd-contaminated soil assisted by tea saponin and plant growth-promoting rhizobacteria - Jie Yu; Ruolan Xie; Jiang Yu; Huan He; Siwei Deng; Senxu Ding; Xiaoshuang Sun; Hameed Hllah (Journal of Soils and Sediments, 2023)

Boosting the photocatalytic hydrogen evolution and NO removal via synergistic effects of in-situ Pt NPs formation and titanium integration in Zr-Porphyrin MOFs - Ruolan Li; Zongqian Wu; Ya Chen; Xingyan Liu; Weiwei Guo; Yumin Huang; Min Fu; Youzhou He (Fuel, 2023)

Molecular encapsulation of cinnamaldehyde in V-type starch: The role of solvent and temperature - Qing Gao; Yanan Sun; Ruolan He; Jiabao Zheng; Bin Zhang; Chin Ping Tan; Xiong Fu; Qiang Huang (Food Hydrocolloids, 2023)

The combined effect of titanium dioxide nanoparticles and cypermethrin on male reproductive toxicity in rats - Yuxin Li; Mingqing Zhong; Xianzhi He; Ruoyu Zhang; Yu Fu; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Environmental Science and Pollution Research, 2022)